Why can the auroral-type sporadic E layer be detected over the South America Magnetic Anomaly (SAMA) region? An investigation of a case study under the influence of the high-speed solar wind stream - Da Silva, L. A.; Shi, J.; Vieira, L. E.; Agapitov, O. V.; Resende, L. C. A.; Alves, L. R.; Sibeck, D.; Deggeroni, V.; Marchezi, J. P.; Chen, S.; Moro, J.; Arras, C.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
The low-electron flux variability (increase/decrease) in the Earth's radiation belts could cause low-energy Electron Precipitation (EP) to the atmosphere over auroral and South American Magnetic Anomaly (SAMA) regions. This EP into the atmosphere can cause an extra upper atmosphere's ionization, forming the auroral-type sporadic E layers (Esa) over these regions. The dynamic mechanisms responsible for developing this Esa layer over the auroral region have been established in the literature since the 1960s. In contrast, there are several open questions over the SAMA region, principally due to the absence (or contamination) of the inner radiation belt and EP parameter measurements over this region. Generally, the Esa layer is detected under the influence of geomagnetic storms during the recovery phase, associated with solar wind structures, in which the time duration over the auroral region is considerably greater than the time duration over the SAMA region. The inner radiation belt's dynamic is investigated during a High-speed Solar wind Stream (September 24-25, 2017), and the hiss wave-particle interactions are the main dynamic mechanism able to trigger the Esa layer's generation outside the auroral oval. This result is compared with the dynamic mechanisms that can cause particle precipitation in the auroral region, showing that each region presents different physical mechanisms. Additionally, the difference between the time duration of the hiss wave activities and the Esa layers is discussed, highlighting other ingredients mandatory to generate the Esa layer in the SAMA region.